Kontribusi Kelentukan Terhadap Keterampilan Smash Permainan Bulu Tangkis Di SMP Negeri 12 Kota Bengkulu - Muhammad Ilhan Indrawan; Dwingki Marta Putra; Azizatul Banat; Bihannudin Bihannudin (Educative Sportive, 2026)
This study aims to determine the contribution of flexibility to badminton smash skills at SMP Negeri 12 Bengkulu City. This research method is Correlation research. The research sample amounted to 20 people. The instrument used in this study was a test of flexibility and badminton smash skills. Where the results of research on flexibility to badminton smash skills at SMP Negeri 12 Bengkulu City have a contribution of 90.80% which means that the flexibility test can be used as a measuring tool to improve badminton smash skills at SMP Negeri 12 Bengkulu City.